2005
DOI: 10.1111/j.1349-7006.2005.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese multicenter phase II study of CHOP followed by radiotherapy in stage I–II1, diffuse large B‐cell lymphoma of the stomach

Abstract: CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) followed by radiotherapy is regarded as standard care for localized aggressive lymphoma; however, prospective confirmation of its applicability to localized primary gastric lymphoma is inadequate, and most patients in Japan have been initially treated with gastrectomy. We conducted a multicenter phase II study to evaluate the feasibility and efficacy of the non-surgical treatment. P rimary gastric lymphoma (PGL) is the most common among extranoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In Japan, a multicenter phase II study involving 52 patients with primary gastric DLBCL was conducted to evaluate the feasibility and efficacy of nonsurgical treatment (three cycles of CHOP followed by radiotherapy to 40.5 Gy). A complete response was achieved in 92% (48/52) of patients, and 2-year progression-free survival and overall survival were 88% and 94%, respectively [2]. These findings suggested that stomachpreserving treatment should be considered a reasonable therapeutic option [5][6][7].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Japan, a multicenter phase II study involving 52 patients with primary gastric DLBCL was conducted to evaluate the feasibility and efficacy of nonsurgical treatment (three cycles of CHOP followed by radiotherapy to 40.5 Gy). A complete response was achieved in 92% (48/52) of patients, and 2-year progression-free survival and overall survival were 88% and 94%, respectively [2]. These findings suggested that stomachpreserving treatment should be considered a reasonable therapeutic option [5][6][7].…”
Section: Discussionmentioning
confidence: 94%
“…A complete response is seen in most patients with localized DLBCL, if treated with combination chemotherapy plus radiotherapy [2,3]. However, some cases are resistant to this therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Two-year progression-free and overall survivals were 88% and 94%, respectively. This organ-preserving treatment should be considered as a very reasonable therapeutic option [17,18]. Lee et al [19] considered that the resection of localized intestinal DLBCL may be appropriate as the primary treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Although radiotherapy in combination with R-CHOP was recommended in some studies, its effectiveness could not be proven in other studies (14,15,(22)(23)(24). Some series suggested that conservative nonsurgical treatment achieves equal or better results than surgery (5,7,8,25).…”
Section: Discussionmentioning
confidence: 99%